Tachydromia incompleta ... - Shamshev, Igor V.; Grootaert, Patrick (Zenodo, 2024)
Tachydromia incompleta (Becker) (Fig. 9) Tachista incompleta Becker, 1900: 33 (♀), Pl. 2, fig. 1. Type locality: Russia, “Insel Nikander” [= Nikandrovskie Islands, mouth of Yenisei River, Krasnoyarskiy Territory]. Tachydromia anderssoni Chvála, 1970: 494, figs 73–75. Type locality: Sweden, Karesundo [= Karesuando, Torne lappmark]. Tachydromia incompleta: Chvála, 1975: 242, figs 574–576, 762 (synonymy of T. anderssoni). Notes on type series. The holotype of T. incompleta is deposited in Helsinki (MZH) and was examined by I.S. in 2019. In addition, the holotype and two paratypes of T. anderssoni were examined in Lund (MZLU) and Moscow (ZMMU), respectively. Material examined. NORTH AMERICA. CANADA. Alberta: Dunvegan, N side Peace River, 11– 25.vii.1995, S. Boucher (1 ♀, CNC); same locality, pan trap in grass, 19–28.vi.1995, S. Boucher (1 ♀, CNC). EURASIA. RUSSIA. Altay Republic: middle flow of river Ulandryk, 27.vi.1964, Grunin (1 ♂, ZISP); Kosh-Agach distr., 60 km SSW Kosh-Agach, 2200m, 49°38´N, 88°29´E, ... : Published as part of Shamshev, Igor V. & Grootaert, Patrick, 2024, Revision of the described Nearctic species of the genus Tachydromia Meigen (Diptera: Hybotidae), pp. 151-196 in Zootaxa 5403 (2) on pages 170-172, DOI: 10.11646/zootaxa.5403.2.1, http://zenodo.org/record/10561768 ...